1998
DOI: 10.1002/jlb.64.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide enhances the growth of U937 human leukemic cells through a cyclooxygenase-mediated pathway

Abstract: The mechanisms of exogenous nitric oxide (NO)-enhanced growth of the U937 human myeloid leukemic cells were examined using sodium nitroprusside (SNP) as a NO donor. Treatment with 0.1 mM SNP for 72 h caused a 45 ؎ 2% increase in U937 cell growth with significantly increased S/G 2 ؉M-phase and decreased G 0 /G 1 -phase of the cell cycle. The growth-enhancing effect of SNP was blocked by indomethacin, a cyclooxygenase inhibitor, but not by H7, a broad spectrum kinase inhibitor, or PD98059, a mitogenactivated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…The cDNA was then analyzed for the differential expression of pro-apoptotic genes ( Fig 5 ). It has been shown that, by 24hr 0.5mM of SNAP produces around 100μM of nitrite in the culture medium [ 37 ], which is very close to the NO secreted by RAW264.7 cells in our experiments ( Fig 2 ). Exogenously administered NO significantly upregulated the pro-apoptotic genes such as BAK (35fold), BAX (15 fold), cytochrome-C (12 fold), and caspase-3 (30 fold) when compared to untreated cells ( Fig 5A–5D ).…”
Section: Resultssupporting
confidence: 81%
“…The cDNA was then analyzed for the differential expression of pro-apoptotic genes ( Fig 5 ). It has been shown that, by 24hr 0.5mM of SNAP produces around 100μM of nitrite in the culture medium [ 37 ], which is very close to the NO secreted by RAW264.7 cells in our experiments ( Fig 2 ). Exogenously administered NO significantly upregulated the pro-apoptotic genes such as BAK (35fold), BAX (15 fold), cytochrome-C (12 fold), and caspase-3 (30 fold) when compared to untreated cells ( Fig 5A–5D ).…”
Section: Resultssupporting
confidence: 81%